Total care of trauma patients from triage to discharge at Chang Gung Memorial Hospital: introducing the development of an iconic acute care surgery system in Taiwan - Chi-Hsun Hsieh; Chien-Hung Liao; Chi-Tung Cheng; Chih-Yuan Fu; Shih-Ching Kang; Yu-Pao Hsu; Chih-Po Hsu; Szu-An Chen; Chien-An Liao; Yu-Hao Wang; Ling-Wei Kuo; Chia-Cheng Wang; et al. (World Journal of Emergency Surgery)
Abstract Background The Acute Care Surgery (ACS) model has evolved to provide structured care across trauma, critical care, and emergency general surgery. This innovative model effectively addresses significant challenges within trauma care. Research indicates that trauma surgeons operating under this expanded scope deliver high-quality care while enjoying professional satisfaction. This article discusses the introduction of the ACS model in Taiwan. Main Body Before the 1990s, Taiwan’s trauma care system relied on general surgeons who operated under an “on-call” model, lacking dedicated trauma specialists. Significant reforms were initiated in 2009, when the government implemented a grading system for hospital emergency capabilities, categorizing hospitals into three levels: General (offering 24 h services), Intermediate (capable of managing stable trauma cases), and Advanced (providing comprehensive care for critically ill patients). All medical centers are classified as advanced level hospitals and are equipped with trauma teams. However, these trauma teams operate under various models, ranging from those focused exclusively on trauma to others with comprehensive responsibilities. The trauma center at Chang Gung Memorial Hospital (CGMH) adopted a comprehensive ACS model, encompassing the entire spectrum of care from emergency admission to discharge, all led by trauma surgeons. This approach ensures continuity and coordination in trauma patient care. Additionally, the model integrates emergency general surgery and surgical critical care, broadening the scope of practice for trauma surgeons and enhancing their overall capabilities, providing significant flexibility in their career paths. The ACS model implemented at CGMH has achieved remarkable success, establishing it as a leading trauma center in Taiwan. Conclusion The emergence of the ACS model aims to reverse the decline in the trauma field that began decades ago. This model not only helps retain skilled professionals but also maintains the expertise of trauma surgeons, ensuring that trauma patients receive the highest quality of care.